2016
DOI: 10.1007/s11999-015-4361-3
|View full text |Cite
|
Sign up to set email alerts
|

How Does the Level of Sacral Resection for Primary Malignant Bone Tumors Affect Physical and Mental Health, Pain, Mobility, Incontinence, and Sexual Function?

Abstract: Background En bloc resection for treatment of sacral tumors is the approach of choice for patients with resectable tumors who are well enough to undergo surgery, and studies describe patient survival, postoperative complications, and recurrence rates associated with this treatment. However, most of these studies do not provide patient-reported functional outcomes other than binary metrics for bowel and bladder function postresection. Questions/purposes The purpose of this study was to use validated patient-rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 23 publications
(36 reference statements)
2
35
0
Order By: Relevance
“…These results suggest that sacrificing the S3 nerve roots would decrease the patients' physical health. A recent study, using the same questionnaire, showed comparable results for physical health, but not for mental health [22]. Several studies done from a physiological point of view show that the sparing of S3 is necessary for normal function of bowel, bladder function, and sexual function [5,8,9,11,25].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…These results suggest that sacrificing the S3 nerve roots would decrease the patients' physical health. A recent study, using the same questionnaire, showed comparable results for physical health, but not for mental health [22]. Several studies done from a physiological point of view show that the sparing of S3 is necessary for normal function of bowel, bladder function, and sexual function [5,8,9,11,25].…”
Section: Discussionmentioning
confidence: 89%
“…Patients were divided into five groups based on the most caudal nerve root spared: L5 (N = 10), S1 (N = 22), S2 (N = 17), S3 (N =18), and S4 (N = 7) ( Table 1). All 33 patients (46%) of the preliminary study [22] were used in this study, although the distribution among the study groups is different because of the different study group inclusion criteria (that is, level of bony cut versus nerve roots spared). The operation reports were reviewed retrospectively to identify which nerve roots were resected.…”
Section: Patientsmentioning
confidence: 99%
“…The authors of the current study recognized the lack of knowledge in the field and have focused on this difficult problem, following previous work [5,8] on patients with metastatic spine disease and assessment of function after sacrectomy based on the level of bone resection. This is unquestionably a novel area of research and their results are quite interesting, despite the usual difficulties with collecting thorough and homogeneous data and maintaining statistical power when analyzing patients' subgroups.…”
Section: Where Do We Need To Go?mentioning
confidence: 99%
“…The impact of these major surgeries on neurological, physical, psychological, social, and emotional functioning is substantial and can have a major impact on a patients’ quality of life [7, 27, 31, 36, 44]. It is important to accurately measure these outcomes in order to: (1) understand the impact of treatment on patients, (2) educate future patients, and (3) compare treatments.…”
Section: Introductionmentioning
confidence: 99%